Spiritual coping, psychosocial adjustment, and physical health in youth with chronic illness: a meta-analytic review. Issue 2 (2nd April 2016) - Reynolds, Nina; Mrug, Sylvie; Wolfe, Kelly; Schwebel, David; Wallander, Jan
ABSTRACT: Objective : The current systematic review and meta-analysis aimed to assess the strength of the relationships between religious/spiritual coping strategies and psychosocial adjustment and physical health in youth with chronic illness. Background : Faced with medical stressors and uncertainty about their illness, spiritual beliefs and behaviours are important for youth with chronic illness. Research suggests that some spiritual coping strategies are helpful (positive), while others are not (negative), and these dimensions of spiritual coping are important predictors of functioning among youth with chronic illness. Method : Fourteen studies, published between 1990 and 2015, met inclusion criteria for the meta-analysis and were analysed using both a fixed effects model and random effects model (REM). Results : Findings revealed significant, small to moderate associations between negative spiritual coping and more concurrent internalising problems (REM r = .34), lower quality of life (REM r = −.34), and poorer health (REM r = −.08). Under the fixed, but not REM, the combined effects showed small to moderate significant relationships between positive spiritual coping and fewer internalising problems ( r = −.19) and better physical health ( r = .19). Conclusion : The results reveal that spiritual coping is an important coping strategy for paediatric patients. Consistent with findings among adults with chronic illness, negative spiritual coping puts paediatric patients at risk for psychosocial maladjustment and poorer health. Intervention research is needed to determine if targeting spiritual coping improves health and psychosocial well-being.